THE USE OF FLASHCARD MEDIA IN IMPROVING STUDENTS' ABILITY IN LEARNING VOCABULARY AT ENGLISH CLASS VII AN-NURMANIAH JUNIOR HIGH SCHOOL - Latifah Rakhma Romadhon; Mutiarani; Muhamad Sofian Hadi (Getsempena English Education Journal, 2021)
The purpose of this study was to determine the learning process and increase students' vocabulary skills in learning English using flashcard media in Class VII SMP An-Nurmaniyah. The research method used is classroom action research with the following stages: planning, implementation, observation and reflection. Data collection techniques used in this study are: (1) tests, (2) interviews, (3) observation. The results obtained from this study are that the implementation of the first action learning has not achieved maximum results, it appears that there are still students who are less involved in the use of flashcard media and there are still students who feel confused about what the teacher bothered so that the average score obtained by students in the first cycle was 68, with learning completeness around 72%. By looking at the Minimum Completeness Criteria (KKM) that has been set at SMP An-Nurmaniyah, namely 65, there are 13 people who reach the completeness criteria, meaning only 72%, while according to the KTSP a learning is said to be complete if the completeness score obtained by students is 75% of the total the number of students. Meanwhile, the second cycle has increased with the average score obtained by students in the second cycle is 84, with learning completeness around 100%.